2017
DOI: 10.1186/s12889-016-3963-3
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle factors associated with obesity in a cohort of males in the central province of Sri Lanka: a cross-sectional descriptive study

Abstract: BackgroundObesity has become a global epidemic. The prevalence of obesity has also increased in the South Asian region in the last decade. However, dietary and lifestyle factors associated with obesity in Sri Lankan adults are unclear. The objective of the current study was to investigate the association of dietary and lifestyle patterns with overweight and obesity in a cohort of males from the Central Province of Sri Lanka.MethodsA total of 2469 males aged between 16 and 72 years () were included in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 67 publications
1
16
2
Order By: Relevance
“…14,19,39 In the present study, female sex, a history of cancer, hypertension, diabetes mellitus, hyperlipidemia, smoking habit, appetite, body weight at 20 years of age, frequency of eating out, stressful life events and working days per week, but not the number of teeth, were independent risk factors for being overweight, and most of these factors have been described as risk factors for being overweight in previous studies. 6,11,19,[39][40][41][42][43] Considering these results and background, our results regarding the risk factors for being overweight are also reasonable. Notably, the previous results were derived from cross-sectional studies; therefore, further studies with a prospective cohort design and long-term follow-up are necessary to clarify the association between tooth loss and being overweight.…”
Section: P-valuesupporting
confidence: 75%
“…14,19,39 In the present study, female sex, a history of cancer, hypertension, diabetes mellitus, hyperlipidemia, smoking habit, appetite, body weight at 20 years of age, frequency of eating out, stressful life events and working days per week, but not the number of teeth, were independent risk factors for being overweight, and most of these factors have been described as risk factors for being overweight in previous studies. 6,11,19,[39][40][41][42][43] Considering these results and background, our results regarding the risk factors for being overweight are also reasonable. Notably, the previous results were derived from cross-sectional studies; therefore, further studies with a prospective cohort design and long-term follow-up are necessary to clarify the association between tooth loss and being overweight.…”
Section: P-valuesupporting
confidence: 75%
“…A recent study from South India in adult population of >19 years of age reported prevalence of underweight 22.7% and prevalence of overweight/obese (BMI ≥ 23) 37.0% [27]. Another study of Sri Lankan male population of age 16-72 years, prevalence of overweight/obese (BMI ≥ 23) was found to be 44.1% [15].…”
Section: Discussionmentioning
confidence: 97%
“…A recent study in Bangladesh reported older age, lower education level and poverty are positively associated with underweight while younger age, female gender, higher education level, affluence and urban residence are positively associated with overweight [4]. An study conducted in adult males in Sri Lanka showed that older age, higher family income and higher education level are positively associated with overweight and obesity [15]. Another study in India among women showed that lower socioeconomic status increased the risk of being underweight while higher socioeconomic status increased the risk of being overweight [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher socioeconomic status and the ethnicity of Moors have been identified as factors that more vulnerable to obesity. Besides, obesity leads to many public health problems and increases the economic burden of health care [4].…”
Section: Introductionmentioning
confidence: 99%